Ketertarikan Generasi Millennial Terhadap Gerakan Pro Gender (Studi Kasus Women’s March Jakarta dan Bali Tahun 2018) - Adrianti, Indira Galuh; Erawan, I Ketut Putra; Mahaswari Jayanthi Mertha, AA. Sagung Mirah (Jurnal Nawala Politika, 2019)
ABSTRACT   The social movement called the Women's March which took place in Jakarta and Bali in 2018 which aims to demand women's rights, gender equality, the elimination of violence against women and marginalized groups, is considered as a movement that is quite big that able to attract the attention of many people and renewal sympathizers. Many of the millennials took part in the action of the Women 's March. The purpose of this research is to find out what is the attraction of pro-gender issues for the millennial generation. This study uses a qualitative method with a snowball sampling technique. The theory used is the Millennial Generation Theory and the Theory of Feminism. The results of this study show that the factors of digital technology, media, communication, education, economics, and families are supporting the millennial generation to be interested and understand about pro gender issues. The different characteristics of each individual make the millennial generation different from one another, and for that matters they feel that gender equality must be fought so that women can be treated equally with men.   Keywords: Pro Gender Movement, Millennial Generation, Women’s March.